PENGARUH LAYANAN TERHADAP MOTIF PEMAKAIAN JASA PENGIRIMAN PAKET PADA PT. POS INDONESIA - Roy Irawan (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2020)
The use of package delivery services today is very influential on one's motives for package delivery services, the post office's dedication is arguably very good, because if we examine the performance traces of its services, the post office has long been providing services about package delivery services. research carried out by secondary and primary data collection methods, including observation, interviews, distribution of questionnaires and documentation. the sample needed for this study amounted to 30 people with a random sampling method, the instrument was tested with validity and reliability, then a standardized coefficient of determination process of the two variables was carried out to find the level of relationship and the determinant effect of the variable x on the variable y, while to find out the significance of the effect of the service on the motive for using package delivery services at PT. Pos Indonesia is t-test by looking at the level of significance.